Inaugural Convocation (Institutional Knowledge at Singapore Management University, 2000)
The inaugural convocation ceremony marking the opening of Singapore Management University and the beginning of the academic year. Ceremonies were held on 29 July 2000 at Bras Basah Park, the site of the university’s future city campus. Front row, left to right: Associate Professor Low Kee Yang, Deputy Dean, School of Business; Associate Professor Tsui Kai Chong, Dean, School of Business; Deputy President Tan Teck Meng; Chancellor Lim Kim San; Education Minister Teo Chee Hean; Mr Ho Kwon Ping, Chairman, Board of Trustees; President Janice Bellace; Professor Patrick Harker, Dean, Wharton School of the University of Pennsylvania; and Provost Tan Chin Tiong.